PENGARUH TATA RUANG KANTOR DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS KOPERINDAG KOTA BUKITTINGGI - Putri Shintia Purnama (Jurnal Ecogen, 2018)
This research aims to analyze the influence of office space and work motivation on performance  employee in the Department of  Koperindag of Bukittinggi. This type of research is descriptive and Causative. The population in this study was a employee in the Office of  Koperindag Bukittinggi. Samples technique in this reasearch use technique sampling total population with a total of  39 respon.Types of data used in this research is the primary and secondary data. Data analysis techniques using path analysis using SPSS program version 20. The results of this research show that: 1) influential office space significantly to the performance of the employee, the better Office space allocation in the improve the performance of employees in the service of the Koperindag Bukittinggi. 2) influential work Motivation significantly to the performance of the employees. The higher the motivation given to employees, it will improve the performance of employees in the service of the Koperindag Bukittinggi. 3) influential office space significantly to Work Motivation, if the higher motivation of employees work then it will increase the spirit of employees who work in the service of the Koperindag Bukittinggi. Based on the results of this research advice writers recommend noticed that the light in the Office Setup and add an adequate work facilities so that the willingness of employees in working can increases. Keywords: Office layout,work motivation,employee peformance